Development of novel fluorescent dye molecules based on BODIPY - Hassanain, Hawazen (2019)
This thesis details the synthesis, optical, florescence, electronic properties, solid state arrangement and intermolecular interaction of functionalized 4,4-difluoro-4-bora-3a,4a-diaza-s-indacene (BODIPY) chromophores. Chapter 1 is a concise overview of the structure, synthesis routes, properties, applications, and fundamental concepts of BODIPY fluorophores. The target of Chapter 2 is to functionalize BODIPY chromophores at the 2,6-positions halogen substituents to afford molecules with strong absorbance in the visible spectrum and new electronic properties due to the presence of the heavy atoms on the BODIPY framework. We have investigated the halogenation and subsequent reactions of BODIPY species which are methylated in the 3,5-positions. The use of an excess of the halogenating reagent (N-iodosuccinimide) leads to selective halogenation of the α-methyl groups, which can be post-functionalized via nucleophilic substitution with morpholine, allowing the investigation of the effect of the combination of halogen atoms and non-conjugated tertiary amine substitution. The effect of such substitution on the solid-state arrangements, absorption, fluorescence and electronic properties of these dye molecules is reported. Chapter 3 focuses on halogen bonding interactions in the solid-state structure of halogenated BODIPY compounds. The presence of halogen atoms, BF2 moiety and/or other electron acceptor groups on BODIPY core can lead to interesting halogen bonding interactions in the solid-state structures of such compounds. Therefore, a search of the Cambridge Structural Database (CSD) was performed in order to find experimental evidence for halogen bonding interactions in the solid-state structures of halogenated BODIPY compounds. Hirshfeld surface analyses and fingerprint plots were used to investigate the effect of different substituents on the intermolecular interactions and provide evidence for the occurrence of halogen bonding interactions which exist in crystal structures of BODIPY compounds. The target of Chapter 4 is to functionalize the BODIPY chromophores at the 2,6-positions by pyridyl and pyrimidyl substituents to afford molecules with strong absorbance in the visible spectrum and remarkable fluorescence in solution, thin film, powder and as single crystals. When CuI and 2,6-dipyridyl-1,3,5,7-tetramethyl,8-phenyl-4,4-difluoroboradiazaindacene (pyr-Bodipy) are reacted, a two-dimensional coordination polymer is formed. However, analogous reactions with 2,6-dipyrimidyl-1,3,5,7-tetramethyl,8-phenyl-4,4-difluoroboradiazaindacene (pyrm-Bodipy) afford a three-dimensional, metal-organic framework. The effect of such substitution on the solid-state arrangements, reflectance, fluorescence, infrared spectroscopy (IR), powder X-ray diffraction (XRD), and single crystal X-ray diffraction is reported.